Evaluation of the Effect of Repeated Intravitreal Bevacizumab Injections on the Macular Microvasculature of a Diabetic Patient Using Optical Coherence Tomography Angiography - Ayman G. Elnahry; Ahmed A. Abdel-Kader; Karim A. Raafat; Khaled Elrakhawy (Case Reports in Ophthalmological Medicine)
A 53-year-old female patient with center-involving diabetic macular edema affecting the left eye was imaged using optical coherence tomography angiography (OCTA) in both eyes. She underwent three monthly intravitreal bevacizumab injections in the left eye only and OCTA was repeated in both eyes one month following the last injection and showed decreased vascular density (VD) in the treated left eye but not in the untreated right eye compared to baseline. No further injections were required in either eye, and OCTA was done in both eyes 4 months following the last injection which showed improved VD of the left eye with stable VD in the right. Three monthly intravitreal bevacizumab injections were then required in both eyes; then OCTA was repeated following the last injection and revealed decreased VD in both eyes compared to previous scan. OCTA could be a useful tool for detecting VD changes following bevacizumab injections in diabetics.